Batas Minimum Usia Kawin Ideal Bagi Pria dan Wanita: Studi atas 58 Penetapan Dispensasi Kawin di Pengadilan Agama Yogyakarta Tahun 2011 - Faisal Luqman Hakim (UIN Sunan Kalijaga Yogyakarta, 2013)
A marriage can only be done if the man was 19 years old and women were 16years old. And if there are people who will do the marriage but has not attained the ageof 21, then it must get permission from their parents. And if the marriage do not reach19 years for men and has not reached 16 years for women, it must apply for adispensation to marry Religious Court. The purpose of this law gives the limit for themen and women who will be the creation of marriage is for the benefit of the family andhousehold. But often occurs in people of a marriage that is done by people who have notreached the age of 19 years for men and has not reached 16 years for women. In 2011Yogyakarta Religious Court has issued a dispensation to marry as many as 58determination. That is, an average of 4 to 5 per month determination issued ReligiousCourt of Yogyakarta. Mating the number of dispensations issued the religious court in2011 that became interesting to do further research.This study would like to know what are the reasons for the applicant to applyfor a dispensation to marry in the Religious Court of Yogyakarta, the majority of theparty who filed the application for a dispensation to marry, and how the average age ofthe prospective bridegroom are applying for the marriage dispensation. The results of thisstudy is that a reason to apply for a dispensation to marry because marriage petitionwas rejected by the Office of Religious Affairs (KUA) local because of age who have notreached the minimum when the marriage should still be held because of the reasons thatis urgent in which the prospective bride is already in a state of pregnancy. Party the mostwidely applied for is of the prospective bridegroom, and the average age of the prospectivebridegroom are applying for a dispensation to marry is 17 years and 3 months.